Fluorescence color diversity of great barrier reef corals - Grigory Lapshin; Anya Salih; Peter Kolosov; Maria Golovkina; Yuri Zavorotnyi; Tatyana Ivashina; Leonid Vinokurov; Victor Bagratashvili; Alexander Savitsky (Journal of Innovative Optical Health Sciences, 2015)
A group of variously colored proteins belonging to the green fluorescent protein (GFP) family are responsible for coloring coral tissues. Corals of the Great Barrier Reef were studied with the custom-built fiber laser fluorescence spectrometers. Spectral analysis showed that most of the examined corals contained multiple fluorescent peaks ranging from 470 to 620 nm. This observation was attributed to the presence of multiple genes of GFP-like proteins in a single coral, as well as by the photo-induced post-translational modifications of certain GFP-like proteins. We isolated a novel photo-convertible fluorescent protein (FP) from one of the tested corals. We propose that two processes may explain the observed diversity of the fluorescent spectra in corals: (1) dark post-translational modification (maturation), and (2) color photo-conversion of certain maturated proteins in response to sunlight.